Green Branding Across Borders: A Conceptual Review of Sustainability-Driven International Marketing Strategies - Stefani I. Angmalisang; Andre David turangan; Imanuella Aprilia Palandeng; Alea Nathasia Karenina Wantha Karwu; Indra Pratama Tuangkalu; Raymundus Rambing; Yuki Sinaulan; Lshaday Lamanaga; Rooney nayoan (Penerbit Jurnal Indonesia, 2025)
This study aims to (1) identify drivers prompting firms to adopt green branding in cross-border markets; (2) articulate strategic configurations that reconcile global brand consistency with local cultural adaptation; and (3) assess risks, moderators, and outcomes shaping the effectiveness of sustainability-driven branding internationally. Methods: A systematic literature review (SLR) of publications from 2020–2025 was conducted across Scopus, ScienceDirect, and Google Scholar. From an initial set of over 120 records, 45 articles met inclusion criteria emphasizing journal reputation, cross-border sustainability focus, and conceptual or empirical contribution. Thematic analysis categorized findings into drivers, strategies, outcomes, and risks, while comparative cross-cultural analysis examined studies from Asia, Europe, and the Americas. Results: Key drivers comprise regulatory pressure, stakeholder and investor expectations, generational shifts toward sustainability, and interfirm alliances. Effective strategies combine product innovation and circular-design approaches, certified green supply chains, and dual communication models that maintain a consistent global green narrative while adapting messages to local cultural frames. Digital traceability mechanisms such as QR codes and blockchain enhance transparency but increase exposure to greenwashing in jurisdictions with weak enforcement. Outcomes indicate positive impacts on brand equity, consumer loyalty, and willingness to pay when claims are authentic and third-party verified, although longitudinal evidence on firm value remains scarce. Conclusions: The proposed integrative framework bridges micro and macro perspectives, underscoring verification, digital traceability, and policy support for SMEs as priorities for practice and future empirical research. Future studies should employ comparative longitudinal and mixed-method approaches to validate mechanisms across diverse industry contexts and cultures. globally.